Ian Ramsey on Talk about God - Evans, Donald D. (Religious studies, 1971)
For Ian Ramsey, talk about God raises many philosophical problems:If we are not to use anthropomorphic concepts like love, power, wisdom, we cannot talk about God; but if we do use them, how do we manage to talk of God and not man?' (MJGC152)Believers wish on the one hand to claim that he (God) is indescribable and ineffable, and yet on the other hand to talk a great deal about him. Nay more, when they speak of God they say that he is transcendent and immanent, im passible yet loving, and so on. But if we speak like this, are we talking significantly at all? Here is the Falsification Problem: What kind of talk can this talk about God be, if it permits us to use such conflicting descriptions of God and to continue to use these descriptions in the face of any and all empirical phenomena?' (RL 13-14).